Exploring the link between leader-member exchange and job satisfaction in the laboratory: A case study of nurses at Royal Prima Medan hospital, Indonesia - Arie Siah Putra Siahaan; Sri Lestari Ramadhani Nasution; Ermi Girsang (Jurnal Teknologi Laboratorium)
Job satisfaction is a critical aspect for hospital management, particularly in laboratory settings, as it significantly impacts nurse performance and the quality of laboratory services. Leadership plays a pivotal role in shaping the work environment, where leaders who effectively perform tasks, adopt appropriate leadership styles, and foster positive relationships can create a conducive and comfortable atmosphere for laboratory nurses. This study investigates the relationship between Leader-Member Exchange (LMX) indicators—affection, loyalty, contribution, and professional respect—and job satisfaction among laboratory nurses at Royal Prima Medan Hospital. Employing a descriptive quantitative approach with a cross-sectional design, this research analyzes data using univariate, bivariate, and multivariate methods. The findings reveal that the majority of respondents were over 45 years old (40.6%), predominantly female (85.7%), had a work tenure of less than five years (57.1%), and held a bachelor’s degree (51.5%). The study identified significant relationships between LMX indicators and job satisfaction: affection, loyalty, contribution, and professional respect each demonstrated positive correlations with job satisfaction. Furthermore, these LMX indicators collectively influenced job satisfaction among laboratory nurses. These findings emphasize the importance of effective leadership in laboratory settings to enhance job satisfaction and ensure optimal nurse performance at Royal Prima Medan Hospital.